THE EFFECT OF FINANCIAL KNOWLEDGE AND FINANCIAL ATTITUDE ON FINANCIAL MANAGEMENT BEHAVIOR ON MSME BUSINESS ACTORS IN NORTH TORAJA REGENCY - Gebi Passalempang; Dina Ramba; Jemi Pabisangan Tahirs (OIKONOMIA: Journal of Economics and Management Science, 2023)
This study aims to determine whether the variables Financial Knowledge and Financial Attitude on Financial Management Behavior. The type of research used in this research is descriptive quantitative. The types of data used in this study are primary data and secondary data, with data collection techniques using questionnaires. The data analysis technique used is the data instrument test, classical assumption test, multiple linear regression analysis, hypothesis testing and coefficient of determination test. The results of this study indicate that partially Financial Knowledge has no significant effect on Management Financial Behavior in UMKM Business Actors in North Toraja Regency. While partially Financial Attitude has a positive and significant effect on Management Financial Behavior in North Toraja Regency UMKM Business Actors and simultaneously Financial Knowledge and Financial Attitude have a significant effect on Financial Management Behavior in North Toraja Regency UMKM Business Actors